1996
DOI: 10.1002/mrm.1910360112
|View full text |Cite
|
Sign up to set email alerts
|

A 31P NMR study of preconditioned isolated perfused rat heart exposed to intermittent ischemia

Abstract: Exposure to a short ischemic period (ischemic preconditioning, IP) will protect the heart from damage following a subsequent longer ischemic episode. The aim of the study was to test whether IP is cardioprotective in the setting of repeated ischemia-reperfusion cycles. Thus, Langendorff-perfused hearts, exposed to IP, were subjected to three consecutive ischemia-reperfusion (10/15 min) cycles. Myocardial energetics, manifested by 31P NMR spectroscopy, was correlated with hemodynamics. ATP recovery was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…The tissue pH was determined based on the chemical shift of the Pi signal, in reference to the phosphocreatine (PCr) signal, on a 31 P spectrum that was recorded from the same perfused heart used for hyperpolarized 13 C metabolic investigation, prior to the hyperpolarized medium injection. Previous studies of the isolated rodent heart showed visible distinction between the extracellular and intracellular Pi signals and demonstrated a range of pH values 13,85,86 . This suggested heterogeneity of pH within the isolated perfused heart, which was observed in the current study as well.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The tissue pH was determined based on the chemical shift of the Pi signal, in reference to the phosphocreatine (PCr) signal, on a 31 P spectrum that was recorded from the same perfused heart used for hyperpolarized 13 C metabolic investigation, prior to the hyperpolarized medium injection. Previous studies of the isolated rodent heart showed visible distinction between the extracellular and intracellular Pi signals and demonstrated a range of pH values 13,85,86 . This suggested heterogeneity of pH within the isolated perfused heart, which was observed in the current study as well.…”
Section: Methodssupporting
confidence: 84%
“…Previous studies of the isolated rodent heart showed visible distinction between the extracellular and intracellular Pi signals and demonstrated a range of pH values. 13,85,86 This suggested heterogeneity of pH within the isolated perfused heart, which was observed in the current study as well. In order to evaluate the tissue pH in the current study, it was first necessary to deconvolve and omit the signal of the KH buffer Pi (Pi KH ) from that of the total Pi signal (Pi t ).…”
Section: Spectral Processingsupporting
confidence: 83%
“…About 1 g of FMB with cells were placed in a sterile NMR tube and perfused with the culture medium and a gas mixture of 95% O 2 /5% CO 2 for up to 24 h. As a control, fresh mouse skin was cut into 2 mm wide strips, placed in the NMR tube and perfused with the medium. The 162 MHz 31 P-NMR spectra of the perfused samples were recorded on-line using Bruker AMX-400WB spectrometer (Sharoni et al, 1996). Spectra were acquired using scans accumulated with 1 s delay between the 45°pulses, spectral width of 8.5 kHz and 8000 data points.…”
Section: Light Fluorescent and Confocal Laser Microscopymentioning
confidence: 99%